Galaxy pairs in the Sloan Digital Sky Survey – XIV. Galaxy mergers do not lie on the fundamental metallicity relation. Issue 3 (20th April 2020) - Bustamante, Sebastián; Ellison, Sara L; Patton, David R; Sparre, Martin
ABSTRACT: In recent observational studies, star-forming galaxies have been shown to follow a relation often dubbed the fundamental metallicity relation (FMR). This relation links the stellar mass of a galaxy with its star formation rate (SFR) and its gas-phase metallicity. Specifically, the FMR predicts that galaxies, at a given stellar mass, exhibit lower metallicities for higher SFRs. This trend is qualitatively consistent with observations of galaxy pairs, which have been robustly shown to experience increasing gas-phase metallicity dilution and enhanced star formation activity with decreasing projected separation. In this work, we show that, despite the qualitative consistency with FMR expectations, the observed O/H dilution in galaxy pairs of the Sloan Digital Sky Survey is stronger than what is predicted by the FMR. We conclude that the evolutionary phase of galaxies interacting with companions is not encoded in the FMR, and thus, mergers constitute a clearly defined population of outliers. We find that galaxies in pairs are consistent with the FMR only when their separation is larger than 110 kpc. Finally, we also quantify the local environment of the pairs using the number of galaxy neighbours within 2 Mpc, N 2, and the projected separation to the second closest galaxy, r 2 . We find that pairs are more sensitive to a second companion than to the local galaxy density, displaying less elevated SFRs with smaller values of r 2 .